Understanding mental health practice - Haith, Mark (55 City Road : SAGE: Learning Matters, 2018)
Mental health is a vast and fascinating subject but knowing where to begin can be challenging. This book focuses on the fundamentals of mental health care. It is packed full of 'need-to-know' information that will help students understand what is meant by mental health and wellbeing, be aware of the common mental health problems, as well as the typical interventions and treatment options available. The book focuses in on the most essential knowledge providing the ideal starting point for anyone looking to gain an initial understanding of mental health.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Psychiatric nursing -- Textbooks; Nursing -- Vocational guidance -- Textbooks; Nursing assessment -- Textbooks; Mental health -- Diseases -- Nursing -- Textbooks